Application of Pediatric Risk of Mortality (PRISM) III Score in Predicting Mortality Outcomes - Joshi, Prakash; Agrawal, Sumit; Ghimire, Jagat Jeevan; Shrestha, Pun Narayan; Khatun, Najala; Banjara , Megha Raj (Journal of Nepal Health Research Council, 2024)
Background: Children admitted in a pediatric intensive care unit have a high risk of mortality. Pediatric risk of mortality III score in first 24 hours of admission has increasingly been used to predict mortality. The objective of this study was to evaluate the validity of Pediatric risk of mortality score in prediction of mortality among the patient admitted in pediatric intensive care unit.Methods: This prospective observational study was conducted at pediatric intensive care unit of a government pediatric hospital from January to June 2021. Patients between 1 month to 14 years of age and meeting the inclusion criteria were enrolled. Pediatric risk of mortality III score was calculated within 24 hours of admission. Patients were followed up for outcome measure as survivors and non survivors. Chi square test and logistic regression analysis were used to find the association of predictors and the score.Results: The mean Pediatric risk of mortality III score was lower in survivors than in non-survivors (4.67 ± 3.8 versus 14.10 ± 6.07; p<0.001). Those requiring inotropic and ventilator support have significantly higher mortality [49.4 versus 0.6 (p<0.001) and 81.8 versus 1.5 (p<0.001) respectively]. Minimum systolic blood pressure, abnormal pupillary reflex, increased blood urea nitrogen and decreased platelet were the significant (p<0.001) risk factors. The area under the Receiver Operating Characteristic curve was 0.916±0.024 (p<0.001) and goodness-of-fit test showed no significant difference between observed and expected mortalities (p=0.186). Conclusions: The Pediatric risk of mortality score constitutes a useful prognostic tool in predicting the mortality. Key words: Mortality; pediatrics; pediatric intensive care unit; risk score,